Investigation on the effect of cold drawing process on mechanical properties and structure of seamless steel (Ck60) tube - Niknamian, Sorush (Journal of Applied Science, Engineering, Technology, and Education, 2019)
The cold drawing process is one of the precise metal forming techniques which have attracted attention by many researchers with respect to the given properties such as potential for improvement of mechanical properties of the material, achieving of accurate dimensional tolerances and rise of quality at final surface so that different studies are conducted on properties of various materials in the course of analysis of its effect. Using cold drawing and also exertion of special heat treatment cycle in this investigation, initially the seamless steel tube Ck60 has been produced and then effect of cold drawing has been assessed on the mechanical properties and structure of steel. The production process of seamless steel tube includes two phases of cold drawing which was followed by surface reduction levels 15.1% and 13.7% respectively. In order to analyze mechanical properties, tensile test and hardness-testing was used and metallography test was also employed to observe the structure. The given results indicate that the seamless steel tube Ck60 produced by means of this production process has ultimate tensile strength (1021 MPa), yield strength (950 MPa) and elongation (9%). Moreover, the value of hardness mean was 312 for the final tube in Vickers Hardness Test. The images taken from optical microscopy also show that the final structure of tube is uniform and as perlite ferrite.